Anthropometric characteristics of ILCA 6 sailors at the Summer Olympic Games - Stoyan Bahchevanski (Journal of Applied Sports Sciences, 2025)
This study aimed to determine the typical anthropometric profi le of elite ILCA 6 class sailors at the Olympic Games. To achieve this goal, trends in key anthropometric indicators, such as weight, height, body mass index (BMI), and age of the competitors in this class were analyzed, along with their impact on the fi nal results at the Olympic Games. A sample of 150 Olympic ILCA 6 class sailors took part in this study, with an average age of 25.59 ± 4.83 years, a body height of 171.51 ± 5.02 cm, a body weight of 66.15 ± 3.88 kg, and a BMI of 22.5 ± 1.48 kg/m². These sailors participated in the Olympic Games of 2008, 2012, 2016, and 2021. The data were collected from offi cial results books published by the Organizing Committees of the Olympic Games, which included the age, height, and weight of all sailors. Means and standard deviations were calculated, and Spearman correlation was used to determine the relation between fi nal performances and age, height, weight, and BMI. The fi ndings revealed a moderate negative correlation between performance and age (r = -.336) among female ILCA 6 sailors at the Olympic Games. The results suggested that the dominant anthropometric characteristics were ages between 20 and 28 (63.8%), height between 1.65m and 1.76m (81.4%), and weight between 62 kg and 70 kg (82.7%).